Addressing the role of PKD3 in the T cell compartment with knockout mice - Jiří Koutník; Verena Neururer; Thomas Gruber; Sebastian Peer; Natascha Hermann-Kleiter; William J. Olson; Verena Labi; Michael Leitges; Gottfried Baier; Kerstin Siegmund (Cell Communication and Signaling, 2022)
Abstract Background The Protein kinase D3 (PKD3) has been implicated in signal transduction downstream of the T cell receptor (TCR). However, its role for the activation of primary T lymphocytes has not been elucidated so far. Methods Expression of PKD isoforms in primary murine T cells was determined by RT-PCR and SDS-Page. A germline PKD3-knockout mouse line was analyzed for its immune response to OVA/alum intraperitoneal immunization. Phenotyping of the T cell compartment ex vivo as well as upon stimulation in vitro was performed by flow cytometry. Additionally, cytokine expression was assessed by flow cytometry, RT-PCR and Luminex technology. Results PKD expression in T cells is modulated by TCR stimulation, leading to a rapid down-regulation on mRNA and on protein level. PKD3-deficient mice respond to immunization with enhanced T follicular helper cell generation. Furthermore, peripheral PKD3-deficient CD4+ T cells express more interleukin-2 than wild type CD4+ T cells upon TCR stimulation ex vivo. However, purified naïve CD4+ T cells do not differ in their phenotype upon differentiation in vitro from wild type T cells. Moreover, we observed a shift towards an effector/memory phenotype of splenic T cells at steady state, which might explain the contradictory results obtained with pan-T cells ex vivo and naïve-sorted T cells. Conclusion While PKD3-deficiency in vivo in mice leads to a skewing of the T cell compartment towards a more activated phenotype, this kinase seems to be dispensable for naïve CD4+ T cell differentiation in vitro. Video Abstract